(3GdebOeI GdHQjI aj GSJfHGW GdUfGYI GdLHQjIs - (3CHh GdYHGS CMeO Hf ehSi GdLdGO GdfNdj GdCTYQj GdMfaj, GdLdGO,J (B792 (3g` s
(3ChdgG (B:s
(3ajHOC aj gPg GdUfGYI GdLHQjI HKdGK eSGFd s
(3BNQgG (B:s
(3Je GdcJGH hGddg Gdehab ddUhGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B249 - (3U(B256s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B261s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs